(untitled) (Journal of Industrial and Mechanical Engineering, 2023)
Forest and interface fires are increasingly frequent in areas affected by droughts and high summer temperatures, within the framework of larger scale processes such as the regional “La Niña” phenomenon and global climate change. For this reason, it is of interest to adopt prevention and self-protection measures against this type of fire, as well as analyze the feasibility of reusing treated wastewater in extinguishing the fire. This article highlights prevention and self-protection measures against fires and analyzes the main factors that limit the reuse of treated wastewater in the peri-urban area of the metropolitan area of Buenos Aires (AMBA, Argentina). The management of vegetation in the surroundings of homes and the advanced treatment of wastewater, guaranteeing its disinfection, are some tools to take into account when facing this type of events.